2013
DOI: 10.1177/1745691612474316
|View full text |Cite
|
Sign up to set email alerts
|

School Rankings, Department Rankings, and Individual Accomplishments

Abstract: The outcome of a graduate student's hunt for employment is often attributed to the student's own accomplishments, the reputation of the department, and the reputation of the university. In 2007, a national survey of psychology graduate students was conducted to assess accomplishments and experiences in graduate school, part of which was an assessment of employment after completion of the doctorate (PhD). Five hundred and fifty-one respondents who had applied for employment reported whether they had obtained em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The standing of a PhD supervisor directly influences [8] the future career trajectory, and number of citations, their students receive throughout their career. Also, the standing of a department influences the future employment chances of its PhD graduates, on average, more than the individual achievements of those students [13]. The impact of teacher quality is seen in other areas of education [20,21], although 'PhD supervisor quality' is assessed differently to teacher quality in school and undergraduate education.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…The standing of a PhD supervisor directly influences [8] the future career trajectory, and number of citations, their students receive throughout their career. Also, the standing of a department influences the future employment chances of its PhD graduates, on average, more than the individual achievements of those students [13]. The impact of teacher quality is seen in other areas of education [20,21], although 'PhD supervisor quality' is assessed differently to teacher quality in school and undergraduate education.…”
Section: Plos Onementioning
confidence: 99%
“…Other factors, such as, the reputation of a department [ 9 ], the reputation the group leader [ 10 ], and access to resources and equipment [ 11 ], the number of full-professors on staff [ 12 ] influenced the research output of the academics involved in that group. Less information is available on the impact of student academic ability or prior research training on PhD outcomes: one analysis found that the reputation of a given department was more important for employment outcomes post-PhD than the accomplishments of the student during their studies [ 13 ]. Overall, the evidence available implies that the research environment may have an inordinate impact on the PhD student outcomes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that graduates from SFCUs have few worries about employment. As some studies have argued, employment outcomes and occupational attainment are mainly affected not only by ascribed factors such as family background but also by achieved factors such as individual effort and university reputation (Chan, 2014;Stenstrom et al, 2013). Therefore, the high-quality employment outcomes of graduates from SFCUs depend on at least the following three determinants.…”
Section: Reasons For the Prosperous Employment Outcomes Of Graduates ...mentioning
confidence: 99%
“…The second potential limitation is that the analysis did not address the interlinkage between pedagogy and employability because of its emphasis on the "outputs" of SFCUs. Further research should comprehensively explore the achieved factors, such as individual effort and university teaching (Chan, 2014;Stenstrom et al, 2013), which affect the employment outcomes of graduates from these nontraditional Chinese mixed-culture universities.…”
Section: Limitations and Further Researchmentioning
confidence: 99%
“…First of all, most of them do not subdivide the visible-minority category into its subgroups, which is highly important due to the amount of heterogeneity within this single label. Secondly, the ones that do make more detailed subgroup distinctions base their research on very specific subsamples from which only "niche" conclusions can be made-such as region specific (Krahn & Maximova, 2005), university specific (Grayson, 2004), occupational industry specific (Li, 2012), level of education specific (Twa et al, 2017), or field of study specific (Stenstrom et al, 2013) among others. These types of studies are not as helpful in making conclusions on ethno-racial disparities in Canada's labour market as a whole, because they are too narrow.…”
Section: Previous Research On Recent Graduatesmentioning
confidence: 99%